WHY E-COMMERCE BUSINESS ETHICS NEEDS? - Sahetapy, Wilma Laura (DiH: Jurnal Ilmu Hukum, 2019)
Globalization and free trade supported by advances in telecommunications and informatics technologies have provided wider space. This shows that in Indonesia also gives a good impact for the economy with the advances in technology. Therefore, this technological advancement needs to be supported by the existence of business ethics that have principles that can create trust to consumers so as to provide wider space to the fulfillment of the quality of goods/services in accordance with the desires and capabilities of consumers. Currently it takes business ethics in e-commerce to minimize losses experienced by both parties in e-commerce transactions. The existence of business ethics in e-commerce, consumers can make transactions without hesitation, and can minimize the fraud that often occurs in e-commerce transactions.